المرافقة البيداغوجية كآلية للتواصل بالجامعة - ايمان قريره (جامعة الوادي - University of Eloued, 2025)
"تهدف الدراسة الى دراسة المرافقة البيداغوجية بجوانبها الإعلامي والبيداغوجي والنفسي كآلية للتواصل بالجامعة، وقد انطلقنا من الإشكال التالي: كيف تساهم المرافقة البيداغوجية كآلية للتواصل في الجامعة؟ للإجابة على هذه الاشكالية يمكن ان نطرح الاسئلة الفرعية التالية: - ما دور الجانب الإعلامي للمرافقة البيداغوجية في التواصل بين الإدارة والطلبة؟ - كيف يساهم الجانب البيداغوجي للمرافقة البيداغوجية في التواصل بين الأستاذ والطلبة؟ - كيف تساعد المرافقة البيداغوجية الطلبة في تخطي الصعوبات النفسية؟ وتتمثل فرضيات الدراسة في: تساهم المرافقة البيداغوجية في تحسين عملية التواصل داخل الجامعة - تستخدم الادارة الجانب الاعلامي للمرافقة البيداغوجية في التواصل مع الطلبة. - يستخدم الأساتذة المرافقة البيداغوجية كاستراتيجية تواصلية مع الطلبة. - تساعد المرافقة البيداغوجية الطلبة في تخطي الصعوبات النفسية. وتمثل منهج الدراسة في المنهج الوصفي التحليلي لأنه الأنسب في هذه الدراسة لمعرفة واقع الدراسة وجوانبها ووصفها وتحليلها، أما عينة الدراسة فقد اقتصرت على طلبة سنة أولى ليسانس جذع مشترك حقوق وعلوم سياسية بكلية الحقوق والعلوم السياسية بجامعة الشهيد حمه لخضر بالوادي، وقد تم توزيع 90 استمارة، واسترجاع 85، فيما تم الغاء استمارة واحدة 01، اي عدد الاستمارات المدروسة هو 84 استمارة. وقد توصلت الدراسة الى ان المرافقة البيداغوجية تساهم في تحسين عملية التواصل داخل الجامعة حيث تستخدم الادارة الجانب الاعلامي للمرافقة البيداغوجية في التواصل مع الطلبة، وكذلك يستخدم الأساتذة المرافقة البيداغوجية كاستراتيجية تواصلية مع الطلبة، وأيضا تساعد المرافقة البيداغوجية الطلبة في تخطي الصعوبات النفسية. "The study aims to study pedagogical accompaniment with its media, pedagogical and psychological aspects as a mechanism for communication at the university .We started from the following problem: How does pedagogical accompaniment contribute as a communication mechanism at the university? To answer this problem, we can ask the following sub- questions: - What is the role of the media aspect of pedagogical accompaniment in communication between the administration and students? - How does the pedagogical aspect of pedagogical accompaniment contribute to communication between professor and students? - How does pedagogical accompaniment help students overcome psychological difficulties? The study hypotheses are: - Pedagogical accompaniment contributes to improving the communication process within the university. - The administration uses the media aspect of pedagogical accompaniment in communicating with students. - Professors use pedagogical accompaniment as a communication strategy with students Pedagogical accompaniment helps students overcome psychological difficulties. The study approach was represented in the descriptive and analytical approach because it is the most appropriate in this study to know the reality of the study, its aspects, description and analysis .As for the study sample, it was limited to first-year students of a joint degree in law and political science at the Faculty of Law and Political Science at Martyr Hama Lakhdar University in El Oued.90 forms were distributed and retrieved.85, while one form 01 was cancelled, meaning the number of forms studied was 84. The study found that pedagogical accompaniment contributes to improving the communication process within the university The administration uses the media aspect of pedagogical accompaniment in communicating with students, Professors also use pedagogical accompaniment as a communication strategy with students, Pedagogical accompaniment also helps students overcome psychological difficulties.
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع الاتصال
Keywords: الطالب الجامعي; الأستاذ الجامعي; الاتصال; المرافقة البيداغوجية; pedagogical accompaniment; communication; university professor; university student